L'aveu . The Confession - Gavras, Costa (France, 1970)
Yves Montand plays an East European government functionary, inexplicably imprisoned by his Communist superiors. He is not told why he has been arrested, nor has his wife (Simone Signoret) been informed of his fate. Undergoing psychological torture, Montand is grilled about his wartime activities. At the end of his rope, he agrees to sign several papers that are thrust before him. He eventually discovers that he's to be a defendant in a "show trial" conducted by his government. "The Confession" was based on the true story of loyal communist Arthur London's unjustified purge trial of 1951.